Quarter Life Crisis: Bentuk Kegagalan Ego Merealisasikan Superego di Masa Dewasa Awal - Nail Hidaya Afandi (JURNAL KONSELING GUSJIGANG, 2023)
This research aims to find out the form of the ego failure to actualize superego in people that experienced quarter-life crisis.  No researcher has yet tried to reveal the cause of the emergence of quarter-life crisis reactions judging by the failure of individuals to fulfil the superego's drive for early adult tasks. The results showed that from 27 previous research results concluded that quarter-life crisis arises because the ego in early adulthood fails to fulfil the superego of tasks in early adulthood, which if successfully fulfilled does not give rise to quarter-life crisis reactions as bad feelings or conditions. To avoid unpleasant feelings, people have to push the id as Freud explained and try to realize the superego based on logical dan realistic considerations from the ego.